What if we took a holiday?: Enriching advertising with intelligent voice assistants - Oliveira, P. M.; Guerreiro, J.; Rita, P. (Proceedings of AIRSI 2022: Technologies 4.0 in tourism, service and marketing, 2022)
The Intelligent Voice Assistants (VAs) are the most prominent technology and a fast-evolving disruption on human-computer interaction (Moriuchi, 2019). This technology has become of paramount importance on smart devices and is exponentially rising worldwide with over 8.4 billion VAs expected in 2024 (Laricchia, 2022). Given the spreading technological development, VAs will certainly play a major role for marketers on brands’ communication strategies, advertising effectiveness and purchase intentions. However, how will advertising value be influenced by AI attributes? For this study, a total of 142 Amazon Mechanical Turk (MTurk) VA users volunteered for survey in exchange for a monetary compensation. All constructs’ measurement scales were adapted from previous research and the hypotheses were tested using Partial Least Squares Structural Equation Modeling (PLS-SEM) on SmartPLS 3 (Hair et al., 2010). This study intends to develop a framework to better understand the perceived value of advertising through intelligent VAs, and how the human voice as the anthropomorphic cue is reflected on AI attributes, and how their relationship with advertising value is mediated by parasocial relationship.